The Last Tsar : The Life and Death of Nicholas II - Radzinsky, Edvard; Translated by Marian Schwartz (New York Anchor Books Doubleday, 1992)
Biography of Tsar Nicholas II providing a portrait of the monarch and detailed account of his last days and assassination.
Include Maps and Index